Study of Invasive Plant Species Distribution in Warangal City, Telangana, India : Life Sciences-Botany for Medicinal Science - Saritha Kommidi; Thirupathi Koppula; Sravanthi Yatla; Mustafa Mohammed (International Journal of Life Science and Pharma Research, 2022)
The invasive plant species are non-native organisms which invade natural habitats and destroy the indigenous flora. The invasion of alien plant species into various places is recognized as a major cause of loss of biodiversity, after habitat destruction. The aim of the present investigation is to study invasive flora of city of Warangal, Telangana with detailed study about their nativity, family, habit and distribution. A total of 97 species belonging to 72 genera of 30 families have been recorded as alien species. Among them about 63% are native to tropical America. Fabaceae is the dominant family with 13 species, followed by Asteraceae with 12 species, Convolvulaceae with 8 species, Amaranthaceae, Malvaceae, Solanaceae, Euphorbiaceae with 6 species each. Remaining families are represented by species less than 6. Habit wise analysis of invasive plant species showed that 75% species belongs to herbs, 9% belongs to shrubs, 3% trees, and 2% climbers. Mesosphaerum suaveolens, Parthenium hysterophorous, Alternanthera ficoidea, Senna uniflora, Prosopis juliflora are dominant terrestrial species. Typha domingensis, Eichhornia crassipes are dominant aquatic species observed throughout the study area. Chromolaena odorata, Lanata camara are fast spreading in the city and if they are neglected they can become aggressive in future. Most of these alien species are problematic and causing damage to the ecosystem of the city. Neverthless some of the plants have medicinal value, some as fodder and few are used as fuel plants. Eichhornia crassipes can be used for preparation of environmental friendly products like paper, fabrics. Hence this study helps for early recognition, monitoring and management of invasive plant species in the study area.